Analysis of riluzole’s profile of use in a central hospital in Lisbon - Paróla, Ana (2018)
Purpose: Riluzole is indicated to prolong life or delay the institution of mechanical ventilation in patients with amyotrophic lateral sclerosis (ALS). Clinical studies have shown that this drug prolongs survival, defined as living patients who are not intubated for mechanical ventilation and without tracheotomy. The purpose of this study is to characterize riluzole’s use as well as the user population in order to contribute to a rational and safe use. Patients and methods: Descriptive, observational, retrospective study describing and characterizing the use of riluzole in ALS patients between July 2006 and December 2016 conducted in a Lisbon’s Central Hospital. Results: Over the course of the study period, 77 patients with different phenotypes of ALS received riluzole. The majority of patients (63%, n=49) were male. The median survival was 10.1 months, but 12 patients (16%) remained on therapy for more than 3 years; 65% of patients were lost to follow-up. The mean adherence rate was 91.2%, and the median adherence rate was 99.3%. One patient discontinued therapy due to gastrointestinal intolerance. Dyspnea and cough were the most common side effects, with roughly one third of patients experiencing each, followed by asthenia and hepatic effects. Conclusion: Despite the extended enrollment period, only 77 patients met the criteria for study inclusion. Nonetheless, statistical data regarding our population is in accordance with reported international data. High adherence rates were observed, but 14% of patients discontinued riluzole. In such cases, assessment by a multidisciplinary team is warranted.